A review of safety, health and environmental (SHE) issues of solar energy system - Aman, M.M.; Solangi, K.H.; Hossain, M.S.; Badarudin, A.; Jasmon, G.B.; Mokhlis, Hazlie; Bakar, A.H.A.; Kazi, Salim Newaz (Elsevier, 2015)
Solar energy is one of the cleanest forms of energy sources and considered as a green source of energy. Solar energy benefit ranges from low carbon emission, no fossil fuel requirement, long term solar resources, less payback time and other. However like other power generation sources, solar energy has also some Safety, Health and Environmental (SHE) concerns. This paper presents the overview of solar energy technologies and addresses the SHE impact of solar energy technologies to the sustainability of human activities. This paper will also recommend the possible ways to reduce the effect of potential hazards of widespread use of solar energy technologies.